The Papers of Clarence Mitchell Jr., Volume VI : The Struggle to Pass the 1960 Civil Rights Act, 1959-1960 - Mitchell, Clarence M. (Clarence Maurice), Jr., 1911-1984 (Book collections on Project MUSE., 2022)
The Civil Rights Act of 1960 attempted to rectify loopholes in the 1957 Civil Rights Act that had enabled southern states to continue disenfranchising Black voters and, in Texas, Mexican Americans. The legislation called for federal inspection of voter registration polls and introduced penalties for obstructing a person from registering to vote.